The Influence of Financial Literacy on Small and Medium Enterprises Performance Through Access to Finance and Financial Risk Attitude as Meditation Variables - Stella Asiimwe (Uganda Christian University, 2023)
The Small and Medium-size Enterprises (SMEs) sector has the crucial role to increase economic growth in emerging countries. Then, the purpose of this study was to examine the determinant variable of the SMEs performance namely financial literacy of the manager. This study utilizes access to financial product and financial risk attitude as the mediation variables. This type of research uses a quantitative approach. The samples of this study 59 person who managed the SMEs in Mukono District in Central division. This study found the positive impact of financial literacy, access to finance, and financial risk attitude on the SME performance. This study also found the mediation role of access to finance and the financial risk attitude on the relationship between financial literacy on SMEs performance. From the descriptive of statistics, it is also found that the weakness of the manager of the SME regarding the bank and capital market product. The implication of these findings the government needs to create a program to enhance the level of financial literacy among the manager of the SMEs especially the skills and knowledge regarding the bank product, risk management, and capital market product.
This is a dissertation.